Artificial Skin: Paper Skin Multisensory Platform for Simultaneous Environmental Monitoring (Adv. Mater. Technol. 1/2016). Issue 1 (20th April 2016) - Nassar, Joanna M.; Cordero, Marlon D.; Kutbee, Arwa T.; Karimi, Muhammad A.; Sevilla, Galo A. Torres; Hussain, Aftab M.; Shamim, Atif; Hussain, Muhammad M.
Abstract : Using low‐cost recyclable household materials such as paper and aluminum foil, Muhammad M. Hussain and co‐workers construct a paper‐based artificial skin in article 1600004. The flexible platform comprises a 3D‐stacked architecture, with an array of multi‐purpose pressure, temperature, and humidity sensors. The paper skin is capable of simultaneous real‐time detection of various external stimuli such as pressure, touch, temperature, humidity, proximity, pH, and air flow.